The effect of autologous plasminogen on the rate of healing of chronic skin ulcers in patients with diabetes mellitus and the level of proteins - markers of hypoxia and angiogenesis - Badziukh , Sergiy; Petrenko , Oleg; Bezrodnyi , Boris; Tykhomyrov , Artem (The Ukrainian Scientific Medical Youth Journal, 2023)
chronic diabetic wounds are a complication of diabetes mellitus that develop as a result of the toxic effects of hyperglycemia, which leads to metabolic disorders with the development of immunosuppression, angiopathy, and neuropathy. A considerable amount of experimental data has been accumulated, which indicates that the participation of the plasminogen-plasmin system in wound healing is not only to clear wounds of fibrin clots, but also to fine-tune the activity of cells that ensure an adequate course of all stages of healing. This study was conducted to investigate the effect of autologous plasminogen on the rate of chronic wound healing in patients with diabetic foot syndrome. The study involved 45 patients with purulent necrotic form of diabetic foot. The efficacy of topical application of standard medications was compared with the application of autologous plasminogen. The wound area was measured once every two days until complete healing. To study the molecular mechanisms of plasminogen effect on wound healing, the level of marker proteins of key physiological processes associated with healing, namely hypoxia and angiogenesis, was determined. The levels of protein regulators of angiogenesis (vascular endothelial cell growth factor (VEGF), hypoxia-inducible factor-1α (HIF-1α) and angiostatins) in the skin tissue of wounds at the beginning and end of treatment with autologous plasminogen in patients with chronic diabetic wounds with neuropathic diabetic foot were evaluated. The levels of VEGF, HIF-1α and angiostatins were determined by Western blotting. We have found that wound tissue in patients with chronic diabetic wounds before treatment is characterized by a reduced level of VEGF, which represents the inability of these wounds to regenerate. At the same time, an increased level of HIF-1α and angiostatins is detected. After treatment with autologous plasminogen applications, a significant increase in VEGF expression was observed against the background of a progressive decrease in HIF-1α and angiostatin activity. The results indicate that increased production of angiogenic inhibitors may counteract angiogenesis and contribute to the failure of chronic wound healing. The use of plasminogen applications reduces the level of angiostatins in wound biopsies, which allowed to increase the level of proangiogenic factors. Treatment with plasminogen demonstrated an improvement in the condition of the wound surface and the transition of healing to the proliferative phase due to the initiation of the inflammatory process in wounds. The results of planimetric measurement of the wound area indicate a 5-fold reduction in the time required for complete wound healing in the group receiving plasminogen applications compared to this parameter in the comparison group.